2019
DOI: 10.3389/fneur.2018.01151
|View full text |Cite
|
Sign up to set email alerts
|

Biases in the Visual and Haptic Subjective Vertical Reveal the Role of Proprioceptive/Vestibular Priors in Child Development

Abstract: Investigation of the perception of verticality permits to disclose the perceptual mechanisms that underlie balance control and spatial navigation. Estimation of verticality in unusual body orientation with respect to gravity (e.g., laterally tilted in the roll plane) leads to biases that change depending on the encoding sensory modality and the amount of tilt. A well-known phenomenon is the A-effect, that is a bias toward the body tilt often interpreted in a Bayesian framework to be the byproduct of a prior pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…This is likely due to the weaker reliability of the neck proprioception, which is not mature yet at this developmental stage ( 5456 ), and which caused the visual inputs to be stronger weighted. This behavioral pattern aligns with recent works showing biases in the perception of visual and haptic verticality to unusual body orientations in younger children ( 57, 58 ), which is here confirmed by the younger participant’s inability to stabilize their head vertically while aligning their torso to lateral target positions. The stronger reliance on the visual system we observed in younger children has been shown to disappear in adults, where immersive VR appears to increase the contribution of proprioceptive and vestibular inputs to postural control over vision ( 59 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is likely due to the weaker reliability of the neck proprioception, which is not mature yet at this developmental stage ( 5456 ), and which caused the visual inputs to be stronger weighted. This behavioral pattern aligns with recent works showing biases in the perception of visual and haptic verticality to unusual body orientations in younger children ( 57, 58 ), which is here confirmed by the younger participant’s inability to stabilize their head vertically while aligning their torso to lateral target positions. The stronger reliance on the visual system we observed in younger children has been shown to disappear in adults, where immersive VR appears to increase the contribution of proprioceptive and vestibular inputs to postural control over vision ( 59 ).…”
Section: Discussionsupporting
confidence: 92%
“…This behavioral pattern also comes in line with recent works showing biases in the perception of visual and haptic verticality to unusual body orientations in younger children (58,59), which is here confirmed by the younger participant's inability to stabilize their head vertically while aligning their torso to lateral target positions.…”
Section: Discussionsupporting
confidence: 91%
“…Concordant to these ndings, is the suboptimal integration of cues for navigation in children younger than 8 years of age [56]. Cuturi and Gori [24] have shown that vision and touch are both in uenced by the same vestibular/proprioceptive priors regarding head and body orientation with respect to gravity.…”
Section: Development Of Multisensory Integrationmentioning
confidence: 83%
“…This will form the basis of postural and motor coordination, ne motor control and visual processing [21,22]. As such, vestibular signals may be used to disambiguate con icting or inaccurate information by reconciling diverse signals [23,24]. Hence vestibular function forms the basis of postural and motor coordination, as well as gaze stabilization [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…This will form the basis of postural and motor coordination, fine motor control and visual processing [18,19]. As such, vestibular signals may be used to disambiguate conflicting or inaccurate information by reconciling diverse signals [20,21]. Hence vestibular function forms the basis of postural and motor coordination, as well as gaze stabilization [17,22].…”
Section: Introductionmentioning
confidence: 99%